A particle swarm optimization algorithm for optimal car-call allocation in elevator group control systems - Bolat, Berna; Altun, Oguz; Cortes, Pablo (ELSEVIER, 2013)
High-rise buildings require the installation of complex elevator group control systems (EGCSs). In vertical transportation, when a passenger makes a hall call by pressing a landing call button installed at the floor and located near the cars of the elevator group, the EGCS must allocate one of the cars of the group to the hall call. We develop a particle swarm optimization (PSO) algorithm to deal with this car-call allocation problem. The PSO algorithm is compared to other soft computing techniques such as genetic algorithm and tabu search approaches that have been proved as efficient algorithms for this problem. The proposed PSO algorithm was tested in high-rise buildings from 10 to 24 floors, and several car configurations from 2 to 6 cars. Results from trials show that the proposed PSO algorithm results in better average journey times and computational times compared to genetic and tabu search approaches. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Elevator; Lift; Particle swarm optimization; Elevator group control system; Vertical transportation; GENETIC ALGORITHM; DESIGN; TIME; Computer Science